The PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN PENGGUNAAN, DAN KEAMANAN TERHADAP NIAT PERILAKU PENGGUNAAN QRIS SEBAGAI METODE PEMBAYARAN DIGITAL - Willyanto; Thia; Teddy Rianto L. Gaol (Business, Economics dan Entrepreneurship, 2026)
The rapid development of fintech in Indonesia has made QRIS a preferred choice for digital payments. The purpose of this study is to analyze three variables: perceived usefulness, perceived ease of use, and perceived security, on behavioral intentions to use QRIS. This study employs a qualitative approach based on a review of relevant literature and an analysis of findings from various academic journals. The results suggest that users’ behavioral intentions are positively influenced by perceived usefulness, especially when QRIS is viewed as a fast and efficient payment solution. At the same time, perceived ease of use contributes to higher intention to use, as a simple and user-friendly system reduces barriers to adoption. Users’ intention to use QRIS is strengthened by the convenience of scanning QR codes during payment transactions. Security also plays a crucial role, as a secure system increases user confidence, while weak protection against fraud and phishing reduces their willingness to use QRIS. The findings indicate that behavioral intentions towards QRIS are shaped not only by its usefulness and ease of use, but also by users’ perceptions of system security.